Animals, Law, and Power: Review of Robert Garner and Siobhan O'Sullivan, eds. The Political Turn in Animal Ethics - Johnson, Lisa (Humanimalia, 2019)
Robert Garner and Siobhan O'Sullivan, eds. The Political Turn in Animal Ethics. London: Rowman and Littlefield International, 2016. ₤85.00 hc; ₤29.95 pb; ₤29.95 e-book.